OCCURRENCE OF CTX-M AND SHV GENES IN ESBL PRODUCING GRAM NEGATIVE ORGANISMS CAUSING PYOGENIC INFECTIONS IN A TERTIARY CARE HOSPITAL IN PUDUCHERRY. - DHANDAPANY SENTHIL PRAGASH; MANGAIYARKARASI; LATHA RAGUNATHAN; SAGEERA BANOO; VIJAYA RAYAPU; IVVALA ANAND SHAKER (International Journal of Pharma and Bio Sciences, 2012)
An extended spectrum beta lactamase (ESBL) production among gram-negative bacilli has emerged as a significant mechanism of resistance to oxyimino-cephalosporin antibiotics during the last 3 decades. Detection of common ESBL genes such as CTX-M and SHV by molecular methods in ESBL-producing bacteria and their pattern of antimicrobial resistance can provide useful information about its epidemiology and aid in rational antimicrobial therapy. A total of 138 multi drug resistant clinical isolates of Enterobacteriaceae family obtained from pyogenic lesions were included in the study. Antibiotic susceptibility test, Phenotypic confirmatory methods, Minimum inhibitory concentration and detection of CTX-M and SHV genes by Polymerase chain reaction were performed. Out of 138 samples, 84 were ESBL producers. Among the 84 isolates CTX-M gene was seen in 55 (65.5%) isolates, SHV was seen in 16 (19%) isolates and both CTX-M and SHV was seen in 14 (16.7%). A strict monitoring mechanism of antimicrobial resistance is necessary because of the high rate of prevalence of CTX-M and SHV genes among gram negative organisms causing clinically significant infections.